Controle de um sistema de combate a incêndio através de comunicação GSM e plataforma arduino - Galvão, Paulo Rogério Vieira (Brasil, 2021)
This work aims to develop an automatic remote monitoring device through a fire fighting system, through the interaction between GSM communication and Arduino Platform, enabling the receipt of text messages on a user's mobile phone if they have a fire principle. The system also allows the user to send command to receive information from sensors and to restore the system after controlled fire.Thus, through the study it was possible to present a functional and dynamic solution that enabled the user communication with the mechanism through the telecommunications system.